Social Distance Of Ex East Timor Communities With The Tuapukan Community, In Kupang District East Nusa Tenggara Province, Indonesia - Marselus Robot; Karolus Budiman Jama; Karus Maria Margareta; Imelda H. E. Rimo; Laurensia Ela Puspita (International Journal of Educational Research & Social Sciences, 2021)
The former East Timorese who chose Indonesia as their country are now living in two state imaginations. First, psychological dependence on East Timor as the land of birth, ancestral land, and land of civilization. Second, juridical dependence on Indonesia as the result of the referendum on August 30, 1999. However, social relations between the former East Timorese and local communities are not always harmonious. They are accepted as guests who do not want to go home by the local community. This study measures the social distance between local and ex-East Timorese communities in Tuapukan Village in Kupang Regency, East Nusa Tenggara Province, Indonesia. The theory used is Social Distance proposed by Emory S. Bogardus. Bogardus compiled a scale measuring a person's acceptance of others in the following elements: (1) willingness to marry someone else; (2) socialize closely as a member of the club's comrades; (3) accept him as a neighbor; (4) accept him as a citizen, and 5) visitors/tourists to our country, 6) leave this country. The research population is the Tuapukan community, Kupang Regency which consists of 546 heads of families. This number includes 211 former East Timorese Family Heads. Researchers used the Slovin formula. The desired critical value (limit of accuracy) (percent allowance for inaccuracy due to sampling error) is 5% with a confidence level of 75%. Data collection using a questionnaire. The data is tabulated according to the respondents' answers. Next, the percentage is calculated and analyzed. The results showed that 36.67% of respondents answered that they were not willing to marry their family members with ex-East Timorese. Meanwhile, social distancing is almost non-existent in terms of respondents' willingness to accept ex-East Timorese as office mates. Only 3.33% of respondents answered that they were not willing to accept ex-East Timorese as office mates or in other words 96.67% answered that they were willing to accept ex-East Timorese as office mates.